Efek Nefroprotektif Kombinasi Ekstrak Daun Gedi Merah dan Daun Kumis Kucing pada Tikus Induksi Etilen Glikol - Joni Tandi; Moh. Roem; Yuliet Yuliet (Journal of Tropical Pharmacy and Chemistry, 2017)
Nephroprotective compound is a compound that has the ability to protect the kidneys from kidney disorders caused by free radicals. This research aimed to determine the nephroprotective effect of the combination of Abelmoschus manihot leaves and Orthosiphon stamineus leaves extract as well as to know the effective extract dose combinations as nephroprotective. This research applied Group Random Design with 6 treatment groups consists of 5 tested animals. Group I was normal control. Group II was negative control. All extract groups was given 0,75% of ethylene glycol and 2% of ammonium chloride. Group III was given 100 mg/kg BW of Abelmoschus manihot leaves extract and 200 mg/kg BW of Orthosiphon stamineus leaves extract. Group IV was given 50 mg/kg BW of Abelmoschus manihot leaves extract and 100 mg/kg BW of Orthosiphon stamineus leaves extract. Group V was given 100 mg/kg BW of Abelmoschus manihot leaves extract. Group VI was given 200 mg/kg BW of Orthosiphon stamineus leaves extract. Treatment was given for 14 days and the levels of creatine and urea were measured on day 0, 8 and 15. The results show the nephroprotective effect in all the extract groups, but the most effective one was the group III.